Pemberdayaan Kelompok Asosiasi Pengusaha Industri Kecil (APIK) dalam Penerapan Teknologi Ukiran Laser pada Kerajinan Turunan Kelapa di Sulawesi - Ade Yusupa; Zuldesmi Zuldesmi; Irvan Trang; Muhammad Fachruddin Suharto (I-Com: Indonesian Community Journal, 2024)
The Small Industry Entrepreneurs Association (APIK) in North Sulawesi faces challenges in adopting modern technology to enhance the quality and efficiency of coconut-based crafts. Key issues include limited access to technology, technical skills, and product marketing. To address these challenges, community service team conducted activities involving socialization, training, and laser engraving technology implementation. Training participants were guided in using laser machines to improve product quality and expedite production. Additionally, digital marketing training was provided to help participants expand their product market reach. Training results showed a significant increase in technical skills and participants’ understanding of laser engraving technology. Pretest and posttest results indicated a notable improvement in participants' comprehension. Laser technology proved effective in boosting production efficiency and product quality. This program is expected to continue with support from the Provincial Cooperative and SME Service Center (PLUT-KUMKM) of North Sulawesi, which will provide facilities and market access for APIK artisans.